Reaction center and light-harvesting I genes from Rhodopseudomonas capsulata - Youvan, Douglas C. (1984)
Five structural genes coding for the reaction center (RC) L, M, and H subunits and the two light-harvesting (LH) I polypeptides, B870α and B870β, have been mapped on two restriction fragments from the R-prime plasmid pRPS404. It has been recently shown that enhanced near-infrared fluorescence mutants of Rhodopseudomonas capsulata typically lack RC or LH I polypeptides and that these lesions are marker-rescued by two restriction fragments from the R-prime plasmid: the 7.5-kilobase-pair EcoRI F fragment and the 4.75-kilobase-pair BamHI C-EcoRI fragment. We have now determined the nucleotide sequence of two restriction fragments and have found that the BamHI C-EcoRI B fragment carries the structural genes for the RC L and M subunits and both LH I polypeptides. Forty kilobase pairs away from this locus, the BamHI F fragment (within the EcoRI F fragment) carries the RC H subunit. The structural genes on the BamHI C-EcoRI B fragment are probably transcribed as part of a polycistronic mRNA. All of the structural genes begin with a consensus Shine-Dalgarno sequence and separate AUG start codons, indicating that the structural polypeptides are not cleaved from larger precursor polypeptides.